Pengaruh Label Halal, Religiusitas Dan Harga Terhadap Keputusan Pembelian Produk Makanan Kemasan (Studi Pada Mahasisw Fakultas Ekonomi Dan Bisnis Islam UIN Raden Fatah Palembang) - Fitri Agustina; Hilda Hilda; Mahmud Alfan Jamil (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Consumption is a form of economic behavior by utilizing goods and services to meet their needs. The basic activities carried out by individuals are eating and drinking activities. This is because eating and drinking are the most basic basic needs for every living thing. Economic development in Indonesia is developing quite rapidly, where business people are competing to create products, especially in the field of packaged food. Indonesia, where the majority of the population is Muslim, shows that the largest consumption is held by Muslims, where in Islam the halal product is a top priority, so it is mandatory for all food producers to have halal certificates. Halal food is all types of food that are permitted by Islamic law for consumption. The purpose of this study was to determine the effect of halal labels, religiosity and prices on purchasing decisions for packaged food products. This type of research is descriptive quantitative, data collection using a questionnaire, the respondents in this study were students of the Islamic economics and business faculties of UIN Raden Fatah Palembang. The data obtained in this study were analyzed using multiple linear regression analysis using the SPSS version 23 analysis tool. The results showed that from the t-test the halal label variable ttable was 2.795 > 1.996 and tcount was 0.007 <0.05 meaning H0 was rejected Ha was accepted. From the t-test the religiosity variable t-table was obtained for 2,734 > 1,996 which and tcount was 0.008 <0.05 meaning that H0 was rejected, Ha was accepted. From the t-test, the price variable t-table is 2,356 > 1,996 and tcount is 0.021 <0.05, meaning that H0 is rejected, Ha is accepted. And the results of the F test show that the Halal label, religiosity and price variables simultaneously have a significant effect. This is evidenced by the results showing the Fcount value of 22.138 > 2.74 Ftable. With a significant figure (p-value) 0.000 <0.05. so it can be concluded that H0 is rejected Ha is accepted.